2001
DOI: 10.1093/alcalc/36.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and mortality of heavy drinkers in a general medical hospital unit

Abstract: This study was performed in order to analyse the prevalence, clinical characteristics and mortality of heavy drinkers among hospitalized patients during a 2-year period. Chronic excessive alcohol consumption (daily intake >80 g of ethanol for males and >40 g for females) was found in 278 of 2913 hospital admissions and was strongly associated with the male sex (90.69%). Heavy drinkers were significantly younger than other admissions (15 and 10 years for men and women, respectively), but showed similar mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Heavy alcohol consumption has been shown to negatively impact life expectancy both directly and indirectly (Goldacre et al, 2004;Jarque-Lopez et al, 2001;McDonnell and Maynard, 1985;Ojesjo et al, 1998;Poldrugo et al, 1993;Rehm et al, 2006;Sher, 2005;Wojtyniak et al, 2005). Furthermore the CDC reported that in 2001, there were approximately 75,000 deaths attributable to either excessive or risky drinking in the United States, making alcohol the third leading actual cause of death (Centers for Disease Control, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Heavy alcohol consumption has been shown to negatively impact life expectancy both directly and indirectly (Goldacre et al, 2004;Jarque-Lopez et al, 2001;McDonnell and Maynard, 1985;Ojesjo et al, 1998;Poldrugo et al, 1993;Rehm et al, 2006;Sher, 2005;Wojtyniak et al, 2005). Furthermore the CDC reported that in 2001, there were approximately 75,000 deaths attributable to either excessive or risky drinking in the United States, making alcohol the third leading actual cause of death (Centers for Disease Control, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although selection bias is almost unavoidable in clinical studies of samples of any age, it may be more of an issue in older samples. Heavy alcohol consumption has been shown to negatively affect life expectancy both directly and indirectly (Ojesjo et al 1998; Jarque-Lopez et al 2001; Regier et al 1990; Goldacre et al 2004; Sher 2005; Wojtyniak et al 2005; Rehm et al 2006). It is also possible that the alcoholics who survived into their sixties, seventies, and eighties and volunteer for demanding research studies are also physically healthier than those who do not.…”
Section: Review Of Clinical Studies In Our Laboratoriesmentioning
confidence: 99%
“…Women with AUD are shown to exhibit a later onset of AUD, and more quickly progress to serious AUD problems (Diehl et al., 2007). In comparison to men who are heavy drinkers, women who are heavy drinkers are prone to exhibit serious medical problems, such as liver cirrhosis (Rehm et al, 2010), and have higher mortality rates (Jacques-Lopez et al, 2001). Therefore, it is important for research to continue to progress in determining the forms of treatment that are most efficacious for women with AUD.…”
mentioning
confidence: 99%